Personal scorecards : a performance management model for aligning personal goals and objectives to organisational strategy within the Cape Town Fire and Emergency Service - Henkin, S. M. M.(Stephen Maurice Michael) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPA)--University of Stellenbosch, 2002.